The entrepreneurial process : seeing and seizing opportunities - Nilsson, Nils, 1951- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book provides an understanding of 'opportunity recognition' as a catalyst and crux of the entrepreneurial process. Grounded in research, it introduces the key concepts at the heart of entrepreneurship theory and practice and demonstrates how entrepreneurship differs from management in language, priorities and practice. The book's central framework is mapped around 'seeing and acting on opportunities', where the entrepreneur enters a situation, eventually sees an opportunity and takes it through a process of idea development into an actionable entrepreneurial initiative. This captures the book's four core elements: person, environment, opportunity and process. The Entrepreneurial Process is unique in its explanation of how key concepts are related and how they can be applied practically to business models, plans and action. Case studies from real life organizations, reflective questions and short exercises throughout encourage student learning and enable true engagement with the subject matter, building students' entrepreneurial efficacy. A 'one stop shop' of key theoretical perspectives on entrepreneurship, opportunity recognition and business modelling, this textbook is essential for undergraduate and postgraduate students on introductory entrepreneurship and enterprise courses. Its practical and applied nature also makes it suitable for MBA and Executive Education. Online resources include chapter-by-chapter PowerPoint slides and a test bank of questions"--
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; Success in business; New business enterprises; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Management